First Montgolfier brothers balloon - Molynk, A. (1783)
Postcard featuring a hand-drawn illustrated depiction of a globe-shaped flying balloon. The illustration depicts the first successful public hot air balloon demonstration on June 4, 1783 by French brothers Joseph-Michel Montgolfier (1740-1810) and Jacques-Étienne Montgolfier (1745-1799). This postcard is part of a set originally collected in a scrapbook entitled Album Gravures et Cartes-Postales: Vieux Paris Types Petits Métiers et Cris De La Rue (1909).
Keywords: Montgolfier, Jacques-Etienne, 1745-1799; Aeronautics; Postcards; Illustrated works; Hot air balloons; Montgolfier, Joseph-Michel, 1740-1810; Ballooning